Effects of Oil Contamination on the Physical-Mechanical Behavior of Loess and Its Mechanism Analysis. (7th December 2021) - Zhang, Shibin; Li, Rongjian; Bai, Weishi; Yang, Qiang
Abstract : Oil leakage will not only pollute the soil but also change its physical-mechanical behavior, and loess has complex properties in the environment of oil presence. Artificial loess contaminated by diesel oil is collected as the research object. The physical and mechanical properties of clean loess and contaminated loess, including liquid and plastic limits, permeability, compression properties, and compressive strength characteristics, are estimated through a series of laboratory tests under different oil contents, water contents, and dry densities. Results show that liquid limits, plastic limits, and permeability coefficient of diesel-contaminated loess decrease with the increase of oil content. The compression modulus and compressive strength of diesel-contaminated loess increase with the increase of dry density at the same oil content. Adding diesel oil, the change law of the unconfined compressive strength of contaminated loess is opposite at the two different water contents. The variation of the compression modulus and unconfined compressive strength of diesel oil-contaminated loess is basically identical at the same condition. The findings of this study would be expected to bridge the gap between theory and practice in treatment and remediation of contaminated soil in the region of oil production.